Strategi Produksi Konten Sponsorship di Instagram @kangentennis pada Event Kangen Juara - Asterik, Pelangi Asa; Bayu Suriatmaja Suwanda (J-CEKI : Jurnal Cendekia Ilmiah, 2026)
This study aims to analyze the content production strategy for sponsorships on the Instagram account @kangentennis during the Kangen Juara event. The focus of the analysis covers how the pre-production, production, and post-production stages are designed and executed to produce sponsored content that supports event exposure while meeting the needs of brand sponsors. Data were collected through direct observation, participation during the internship activities, and interviews with relevant parties. The findings show that structured content planning and consistent communication with sponsors play an essential role in producing visual outputs that align with brand identity. Additionally, selecting content formats that match Instagram’s audience characteristics contributes to increased engagement and promotional reach. These results indicate that a systematic content production strategy not only enhances the event’s professional image but also maximizes the value of sponsorship collaboration through social media.